The complete chloroplast genome of Salix matsudana f. tortuosa - Tiantian Yang; Qiang Zhang; Chengjun Yang; Jian Qiu (Mitochondrial DNA. Part B. Resources, 2022)
In this study, the complete chloroplast genome of Salix matsudana f. tortuosa was sequenced and analyzed. The genome of Salix matsudana f. tortuosa was 155,673 bp in length and was quadripartite in structure, containing a large single-copy region with a length of 84,447 bp, a small single-copy region with a length of 16,320 bp, and two inverted repeats of 27,453 bp in length. The chloroplast genome contains 130 genes, including 85 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The GC content is 36.64%. The phylogenetic tree shows that Salix matsudana f. tortuosa, Salix matsudana, and Salix babylonica are closely related and located on the same branch. The chloroplast genome of Salix matsudana f. tortuosa will provide important data for further systematic study of Salicaceae and the genus Salix.